UNDERSTANDING OF LOCAL KNOWLEDGE IN SUSTAINABLE DEVELOPMENT TOWARD GLOBAL PERSPECTIVE (EXPLORATION STUDIES OF JAVANESE CULTURE) - Johannes Adiyanto (Journal of Architecture&ENVIRONMENT, 2014)
The concept of sustainable emerged around 1970 which was developed to address the critical issue of energy. It is less recognized that this concept need to be developed and industrialized by the countries due to their dependence on fossil fuels in that time. Then, architecture develop it into a green building concept. The latest development of green architecture becomes imperative in the design architecture for the construction of new buildings. That understanding built in global perspective, how about in local perspective – like in Javanese culture – is it the same context or perspective? Furthermore, it is going to be the focus of this paper.This paper tries to pick sustainable background in the context of Javanese culture as the focus. In Javanese culture, philosophy background can be constructed by performing puppet plays reinterpretation. Lakon Babad Alas Wanamarta can be placed as the cornerstone of sustainable communities’ the philosophy of Java. Theoretical level and indicators for green architecture in the Java community may appoint Primbon.Research method use Hegel dialogue with architecture critic approach. This working paper is still at the level of exploratory studies to answer unresolved and couldn’t replace sustainable and architectural ideas that have been grown in agrarian people today. But it needs to be examined further as sustainable or green architecture can be developed further from an agrarian society civilized.